2012
DOI: 10.1021/ef3004637
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Studies of Fossil Fuels using One- and Two-Dimensional Methods at High Magnetic Field

Abstract: We examine the opportunities offered by advancements in solid-state NMR (SSNMR) methods, which increasingly rely on the use of high magnetic fields and fast magic angle spinning (MAS), in the studies of coals and other carbonaceous materials. The sensitivity of one-and two-dimensional experiments tested on several Argonne Premium coal samples is only slightly lower than that of traditional experiments performed at low magnetic fields in large MAS rotors, since higher receptivity per spin and the use of 1 H det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(155 reference statements)
2
13
0
Order By: Relevance
“…Note that NMR characterization of fossil fuels has almost exclusively been performed at low magnetic fields, at 9.4 T (corresponding to a 1 H resonance frequency of 400 MHz) or lower and at spinning rates ≤ 20 kHz, because of several potential drawbacks associated with using high fields and high MAS rates [93]. Recent work by Pruski's group [293,294], however, demonstrated that high magnetic fields and fast MAS utilized in coal studies offered some advantages (the possibility of using 1 H detection of 13 C in 2D heteronuclear correlation schemes and simplified pulse sequences), with only slightly lower sensitivity. However, it remains difficult to detect interior aromatic carbons or obtain quantitative 13 C spectra under these conditions.…”
Section: Fossil Fuelsmentioning
confidence: 99%
“…Note that NMR characterization of fossil fuels has almost exclusively been performed at low magnetic fields, at 9.4 T (corresponding to a 1 H resonance frequency of 400 MHz) or lower and at spinning rates ≤ 20 kHz, because of several potential drawbacks associated with using high fields and high MAS rates [93]. Recent work by Pruski's group [293,294], however, demonstrated that high magnetic fields and fast MAS utilized in coal studies offered some advantages (the possibility of using 1 H detection of 13 C in 2D heteronuclear correlation schemes and simplified pulse sequences), with only slightly lower sensitivity. However, it remains difficult to detect interior aromatic carbons or obtain quantitative 13 C spectra under these conditions.…”
Section: Fossil Fuelsmentioning
confidence: 99%
“…We end this section by referring to a recent work by the group of Pruski [112] strengthening the fact that application of ssNMR to the study of coals has mainly been developed in the 80's and since then few innovations have been brought in this field despite the fact that the "NMR tool box" has considerably developed in the past 20 years in terms of accessibility to strong magnetic fields (> 9.4 T), fast MAS (> 30 kHz), newly implemented pulse programs, improved electronics and so forth. For this reason, many classical approaches (e.g., use of TOSS to suppress spinning side bands, use of low magnetic fields) should be revised.…”
Section: Coalmentioning
confidence: 99%
“…This was done, for instance, by us in the study of hydrothermal carbons and detailed later. Reference [112] shows then how structural resolution of various types of coals can be achieved at high fields and fast MAS by proper implementation of CP using, for instance, a tangential ramp to be more efficient in meeting the Hartmann-Hahn condition; it also shows how 2D 1 H- 13 C correlation maps can be obtained in a reasonable amount of time and acquired under advanced homonuclear decoupling schemes like Phase Modulated Lee-Goldburg (PMLG).…”
Section: Coalmentioning
confidence: 99%
“…In the UF-MAS technique, the sensitivity per unit volume is also enhanced by reducing the spectral line width and/or SSBs, and 1 H inverse detection enables obtaining more than 10 times larger spectral intensity than 15 N detection in the case of 1 H– 15 N interaction . However, 1 H– 15 N observation of a natural coal using UF-MAS is assumed to not be feasible because the sample volume for UF-MAS is at most 1 mg; even a 1 H inverse heteronuclear correlation experiment for 13 C in coals, which is the most abundant nucleus in coals and has higher gyromagnetic ratio than 15 N, needs at least 23–68 h, making it very challenging . Therefore, for the detailed assignment of 1 H– 15 N correlation signals of natural coals, 15 N-labeled model coals that have 1D 15 N SPE MAS line shapes comparable to those of natural coals would be needed.…”
Section: Introductionmentioning
confidence: 96%
“…11 However, 1 H− 15 N observation of a natural coal using UF-MAS is assumed to not be feasible because the sample volume for UF-MAS is at most 1 mg; even a 1 H inverse heteronuclear correlation experiment for 13 C in coals, which is the most abundant nucleus in coals and has higher gyromagnetic ratio than 15 N, needs at least 23−68 h, making it very challenging. 12 Therefore, for the detailed assignment of 1 H− 15 N correlation signals of natural coals, 15 N-labeled model coals that have 1D 15 N SPE MAS line shapes comparable to those of natural coals would be needed. Details of the nitrogen structure for natural coals should then be studied based on such 15 N-labeled model coals.…”
Section: ■ Introductionmentioning
confidence: 99%